Simple, concise, stereocontrolled synthesis of (8E,10Z)-pentadecadien-1-ol acetate - Chavan, Subhash P.; Kharul, Rajendra K.; Kamat, Subhash K.; Kalkote, Uttam R.; Kale, R. R. (Synthetic Communications, 2005)
A simple, concise, and stereocontrolled synthesis of (8E, 10Z)-pentadecadien-l -ol acetate involving a Cadiot-Chodkiewicz reaction as the key step is described.
Keywords: acetate; Acrobasis vaccini; Cadiot-Chodkiewicz reaction; diacetylene; Pheromone

Total synthesis of (+)-petromyroxol - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
The total synthesis of (+)-petromyroxol establishing its absolute configuration has been accomplished. The strategy developed employs easily accessible carbohydrate building blocks and comprises flexible and scalable chemistry that allowed the synthesis of (+)-petromyroxol along with its three diastereomers varying the stereochemistry mainly at C5 and/or C6. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Glucose diacetonide; Petromyroxol; Pheromone; Sea Lamprey; Total synthesis